Business Innovation in Health Services: A Literature Review - Tangkudung, Auderey Gamaliel Dotulong; Rante, Jones Zenas; Pakpahan, Marisi; Rowi, Armein Sjuhary (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Business innovation in the health sector has enormous potential to fundamentally change how health services are provided and accessed. In this article, we will discuss the importance of business innovation in improving the quality of health services, opening new opportunities, and facing complex challenges in the global health system. Concrete examples of business innovation include telemedicine technology, handheld health devices, and mobile health applications, which have changed the way health services are delivered and accessed. Despite significant benefits, there are still several challenges such as regulatory compliance, building user trust, and cost and accessibility issues that must be overcome. Collaboration between the public, private, and academic sectors and a deep understanding of the challenges and opportunities are critical to achieving the full potential of business innovation in the health sector.